Analysis of polymeric composite materials for frictional wear resistance purposes. Issue 2 (February 2021) - Majeed, Badeea; Basturk, Suleyman
This research is about manufacturing brake pads from a polymeric composite material composed of domestic materials, which are cheaper and available in the market. An unsaturated polyester is used as the basic material. Styrene–butadiene rubber and montmorillonite clay materials available in the market are used as the fillers. The Kevlar fibers, the nylon, and the steel fibers are used as reinforcing materials to improve the mechanical properties. The Shore hardness, compressibility, thermal conductivity, impact, and wear resistance tests have been implemented. The results show that the hardness, compressive, and impact resistance of the samples increase with the increase of the reinforcement ratio by Kevlar fibers, nylon fibers, and steel fibers. The rate of wear decreases with the increase of reinforcement ratio. The thermal conductivity decreases with an increase in the reinforcement ratio by Kevlar fibers and nylon fibers while the thermal conductivity increases with an increase in the reinforcement ratio by Kevlar fibers and steel fibers. Compared to the commercial brake pads, high strength, high wear resistance, high impact resistance, high hardness, high compressive strength, low thermal conductivity, and low-cost brake pads have been proposed.